La relación entre las transferencias por canon a los gobiernos regionales con la pobreza monetaria en Loreto 2007-2021 - Arevalo Torres, Franks Jonhatan (2024)
This research analyzes the relationship between mining and oil canon transfers and monetary poverty in the region of Loreto, Peru, from 2007 to 2021. Despite the significant increase in these transfers due to the intensification of extractive activities, Loreto continues to face high levels of poverty. The study uses an econometric approach to examine the effectiveness of canon transfers in reducing monetary poverty, as well as to identify other socioeconomic factors that influence this dynamic. In addition, the possible indirect impact of the economic dependence generated by these transfers and its effect on the productive structure of the region is evaluated. The results point to a complex interaction between canon allocations and poverty indicators, suggesting that, although transfers contribute to development, their management and the implementation of complementary policies are crucial to achieve a more significant impact on social well-being. This study provides valuable insights for public policy formulation, emphasizing the need for inclusive, equitable and sustainable development strategies that leverage canon revenues for the real progress of communities in Loreto and similar regions.